DYSTOCIA DUE TO FETAL ANASARCA FOETUS ALONG WITH NORMAL FOETUS AND ITS SUCCESSFUL SURGICAL MANAGEMENT IN A GOAT – A CASE REPORT - J, ARUNPANDIAN; J, DENNY; N, SRIVASTAVA; M, GANESAN (The Indian Journal of Animal Reproduction, 2023)
A 5-year-old female non-descript goat was presented to Referral Veterinary Polyclinic, ICAR-Indian Veterinary Research Institute in Bareilly, with signs of anorexia, restlessness and severe straining. The first water bag was reportedly observed externally two hours before the presentation of the animal to the clinic. On per-vaginal examination the foetus was oedematous and bloated with no suckling and corneal reflexes. The condition was diagnosed as foetal anasarca through the per-vaginal examination and could not be removed per vaginally by traction. The condition was managed successfully by surgical intervention and the animal had an uneventful recovery.